Analisis Exchange Market Pressure Di Indonesia - Nur Annisa; Tiara Nirmala (Goodwood Publishing, 2022)
Exchange Market Pressure is defined as the occurrence of excess supply or disequilibrium in the money market, which is indicated by the depreciating value of a country's currency and reducing foreign exchange reserves. This study aims to analyze the Exchange Market Pressure in Indonesia by looking at the relationship, impulse response function, and variance decomposition. This study uses secondary data taken from the website of Bank Indonesia and the Central Statistics Agency. The analytical tool used is the Vector Error Correction Model. The results show that in the long-term relationship, domestic credit growth and the BI rate have a significant positive relationship, GDP growth has a significant negative relationship, while the current account balance is not significant to Exchange Market Pressure. And the results of the study show that in the short term, domestic credit growth has a significant positive relationship, GDP growth, current account balance, and the BI rate have a significant negative relationship. Meanwhile, the EMP responded negatively to the shock of the BI rate, while based on variance decomposition, the biggest influence came from the GDP growth variable.